Isolation and culture of decidual natural killer cells from term placenta and complete hydatidiform mole. (March 2022) - Lakatos, Kornél F.; Hasselblatt, Kathleen; Fülöp, Vilmos; Végh, György Lajos; McElrath, Thomas; Berkowitz, Ross S.; Elias, Kevin M.
Highlights: Decidual uterine natural killer cells can be isolated from term placenta or molar tissue. Mechanical and enzymatic degradation, followed by cell sorting, greatly enhances cell yield and purity. Isolated natural killer cells can be maintained in culture and used for functional assays. Abstract: Decidual natural killer cells (dNK) have been the focus of many studies because of their unique roles in both the anti-tumor immune response and healthy placental formation. Revealing the immunological mechanisms by which they interact with their target cells may lead to a better understanding of immune evasion of certain tumor cells, including abnormal cells of the different forms of gestational trophoblast disease and miscarriages of immunologic origin. Efforts to perform functional immunological studies on dNK cells have been limited by difficulty obtaining sufficent quantities of cells and sustaining the dNK phenotype. A novel protocol was developed to isolate and culture dNK cells from fresh, term placentas and complete hydatidiform moles.The placental samples were collected from healthy women undergoing scheduled elective cesarean delivery. The molar samples were collected after evacuation and curettage. Tissue samples were made into single cell suspensions using mechanical and enzymatic degradation, followed by fluorescence-activated cell sorting (FACS) using surface markers. The dNK cells were then expanded in cell culture. Their surface markers and cytotoxicity were reassessed by flow cytometry and functional assays. The protocol produces high quantities of enriched dNK cells which can be sustained in cell culture for at least a month, preserving their phenotype and funcionality for a week.